Two-Dimensional Numerical Study on the Migration of Particle in a Serpentine Channel - Yi Liu; Qucheng Li; Deming Nie (Journal of Nanotechnology)
In this work, the momentum exchange scheme-based lattice Boltzmann method is adopted to numerically study the migration of a circular particle in a serpentine channel for the range of 20 ≤ Re ≤ 120. The effects of the Reynolds number, particle density, and the initial particle position are taken into account. Numerical results include the streamlines, particle trajectories, and final equilibrium positions. Close attention is also paid to the time it takes for the particle to travel in the channel. It has been found that the particle is likely to migrate to a similar equilibrium position irrespective of its initial position when Re is large. Furthermore, there exists a critical solid-to-fluid density ratio for which the particle travels fastest in the channel.